Study on Medicinal Plants Used by the Ethnic Mamuju in West Sulawesi, Indonesia - Syamsiah, Syamsiah; Hiola, Siti Fatmah; Jumadi, Oslan; Mu’nisa, Andi (Department of Agronomy and Horticulture, IPB University, 2016)
Indonesia is known as a country with very high biodiversity, within which are potential medicinal plants that have not been fully explored or utilized. The potential of this natural biodiversity for the health and welfare of the Indonesian community is regarded as high, if it is properly utilized. An example of the potential benefits of these plants is reflected in the types of traditional medicinal plants used by the Mamuju ethnic in West Sulawesi. This research aims to describe the types of plants used as traditional medicines by the Mamuju ethnic group. The study is based on descriptive approach that used a combination of observations, interviews and taxonomy. The results of the study revealed that there are 31 species of medicinal plants used as sources of traditional medicine by the Mamuju ethnic group, of which there are 33 medical herbs used for the treatment of 31 kinds of diseases. The health issues that are addressed through the use of medicinal plants include the treatment of some types of internal diseases, including cysts, cancer, tumors, high blood pressure, ulcers and diabetes; disease symptoms such as itching, swelling, myopic, new injuries and infections. Some traditional medicines are used in relation to onset of menstruation, and postpartum treatment. The plant components that are used for medicinal purposes include roots, stems, stem bark, leaves, flowers, fruit, seeds, rhizomes and tubers. However, the predominant plant component used for medicinal purposes is plant leaves.